A miniaturized, self-sustaining, and integrable bio-solar power system. (June 2020) - Mohammadifar, Maedeh; Tahernia, Mehdi; Choi, Seokheun
Abstract: We demonstrate a practical and sustainable bacterial power source for low-power electronic applications. Self-sustainable electricity is produced from revolutionarily structured microliter-scale bio-solar cells using a co-culture of heterotrophic and autotrophic bacteria. Two bio-solar cells are integrated on a single chip and connected in series, continuously generating light-responsive electricity from heterotrophic bacterial respiration with the organic substrates produced by photosynthetic autotrophs. Agar-based anolyte, catholyte, and salt-bridge provided solid-state ionic environments for more efficient syntrophic interactions between co-cultures without bacterial competition, further enhancing the device performance and lifespan. The solid-phase platform allows versatile device configuration in a small footprint without a cumbersome fluidic feeding system and permits easy integration and operation with solid-state applications. The device is sealed with a gas-permeable polydimethylsiloxane (PDMS) membrane to facilitate gas exchange to the bacteria and cathodic reactions, even ideally allowing for replenishing bacterial gasses from environments for self-sustainable energy harvesting. A DC-DC booster circuit is integrated with the stacked bio-solar cells to increase the operational voltage (~500 mV) to a maximum output of >3 V for self-powering an on-chip, light-emitting diode (LED). This is the first demonstration of the microliter-scale bio-solar cell as a practical power source. Graphical abstract: Image 1 Highlights: A practical and sustainable bacterial power source is developed for low-power electronics. The device uses the syntrophic interaction between autotrophs and heterotrophs. It provides solid-phase ionic pathways in solid-state microfluidic chambers.